(3x+13)=(3x+13)

Simple and best practice solution for (3x+13)=(3x+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+13)=(3x+13) equation:



(3x+13)=(3x+13)
We move all terms to the left:
(3x+13)-((3x+13))=0
We get rid of parentheses
3x-((3x+13))+13=0
We calculate terms in parentheses: -((3x+13)), so:
(3x+13)
We get rid of parentheses
3x+13
Back to the equation:
-(3x+13)
We get rid of parentheses
3x-3x-13+13=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 49+2m=6(+m)+9 | | (6/x)+(8/x+8)=3 | | 70x-10=66x+22 | | 5k+11=-19-k | | x+6/3=x-2/5 | | (x+3)=14-7 | | 19=10-4w-7 | | X=1/6y-1/2 | | -2s+3=5s+21 | | 15x+40=1299 | | -3p-22=9p-4 | | X;4x+16=95 | | 9x−8=4x+7 | | -42x-6(-2x-17)=22 | | 9t-4=7 | | 10w+360=430 | | 3t-5=12 | | 144=y+35 | | 7a+17=1-9a | | 42=x-37 | | 4p+20=52 | | 20-(4x+3)=4x+7 | | 62=-3x-7(x-16) | | x^2=-235.2 | | c/12-4=16 | | 11x^2+10=2x+10x^2+3 | | 5+5r-3=22 | | 11x^2+10=2x+10x^2 | | 3n-17=n-1 | | 3(x-4)=12. | | -7=y+25 | | c/5-8=-12 |

Equations solver categories